Consideration of Age Is Necessary for Increasing the Accuracy of the AJCC TNM Staging System of Pancreatic Neuroendocrine Tumors - Wang, Zhengshi; Jiang, Wenli; Zheng, Lijuan; Yan, Jie; Dai, Jiaqi; Huang, Caiguo; Zhang, Qian; Yin, Zhiqiang; Gong, Xiangnan; Zhang, Yun (Frontiers in Oncology, 2019)
Purpose: Currently, of the two most common staging systems of pancreatic neuroendocrine tumors (pNETs) one is from the European Neuroendocrine Tumor Society (ENETS) and the other is from the American Joint Committee on Cancer (AJCC). However, there are imperfections in both these staging systems. Patients and methods: Patients were selected retrospectively from the Surveillance Epidemiology and End Results (SEER) database (2004 to 2013). The effect of age on the hazard ratio (HR) was evaluated using restricted cubic splines. The discriminatory power of the staging systems was determined using the concordance index (C-index). Results: A total of 3,034 patients with pNETs were included in the final analyses. The risk of death increased slowly along with age for patients under 60 years of age, but the risk of death rose sharply for those over 60 years of age, forming a mirrored L-shaped survival curve. In the current AJCC tumor-node-metastasis (TNM) staging system, no statistical significance was observed between stages IA and IB (p=0.105). Patients with stage IIB even had longer OS than patients with IIA, although there was no statistical significance (p=0.574). The proportion of stage III patients was small (2.7%). In the proposed aTNM staging system, significant survival differences could be observed among stage I, IIA and IIB (p<0.001) and the proportion of stage III rose from 2.7% to 25.7%. Conclusion: Our findings suggest that age has a critical influence on the survival of patients with pNETs. Age should be considered as a factor in future staging systems of pNETs.